Coccidiose em ruminantes: tratamento metafilático e diagnóstico molecular - Reginato, Caroline Zamperete (2020)
Eimeria spp. infection is one of the main diseases that affect young ruminants. Eimeriosis is responsible for considerable economic losses, due to the reduction of weight gain and compromising the development of young animals, mainly due to subclinical infections. This condition occurs especially in intensive and semi-intensive livestock with high animal density, but outbreaks in extensive livestock are also reported, less frequently. Coccidiosis control can be accomplished using treatment that interrupt the life cycle of the parasite na with sanitary practices, both aiming decrease the environment contamination. In this context, this thesis presentes two chapters, with evaluated: (1) the effectiveness of metaphylactic treatment with 5% toltrazuril in beef calves naturally infected with Eimeria spp. created extensively; (2) Six different protocols for extracting DNA from Eimeria spp. for molecular diagnosis in cattle and sheep. Chapter 1 presents a study in which four different metaphylactic treatments with 5% toltrazuril were evaluated, in calves from birth to weaning. 92 animals were used, which were divided into 4 experimental groups: I — treated at both birth and weaning; II — treated at birth but not treated at weaning; III — not treated at birth but treated at weaning; and IV — neither treated at birth nor at weaning (control). Less oocyst exception was observed in the treated group up to 75 days, and at 150 days of age, in addition to a positive correlation between the presence of diarrhea and oocyst count in the feces. There was no difference in weight gain of animals in any of the study periods. Chapter 2 presents a study in which twenty pools of fecal samples from cattle (10 pools) and sheep (10 pools) were distributed to six DNA extraction protocols: commercial kit, commercial kit with modification, DNAzol, cetyl-trimethyl ammonium bromide (CTAB), glass beads and commercial kit for fecal samples. Among the tested protocols, CTAB was determined to be most suitable for DNA extraction from oocysts, with 90% of DNA detection by PCR.